2009
DOI: 10.1007/s10750-008-9687-3
|View full text |Cite
|
Sign up to set email alerts
|

Diatom teratological forms and environmental alterations: a review

Abstract: The foremost feature of a diatom is the species-specific ornamentation of the silicon cell wall,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(96 citation statements)
references
References 167 publications
6
79
0
11
Order By: Relevance
“…Indeed, diatom teratological forms in unstable microhabitats are quite common (Falasco et al 2009). For instance, rusHFortH et al (1984) noticed abnormalities in the horse-shoe area (or "sinus") in Planothidium lanceolatum (BréBisson ex kützInG) lanGe-Bertalot collected from walls in lava tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diatom teratological forms in unstable microhabitats are quite common (Falasco et al 2009). For instance, rusHFortH et al (1984) noticed abnormalities in the horse-shoe area (or "sinus") in Planothidium lanceolatum (BréBisson ex kützInG) lanGe-Bertalot collected from walls in lava tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic identification mainly followed Lavoie et al [34]. Diatom frustule deformations were noted and classified as (i) irregular valve shape, (ii) irregular raphe, (iii) irregular striae, (iv) mixed [35].…”
Section: Water Chemistry and Diatom Assemblage Analysesmentioning
confidence: 99%
“…Does FA (or even DA) increase during successive vegetative divisions, thereby resulting in accumulating irregularities in the shape of the siliceous frustules? It has been shown that teratogenic morphological asymmetry of diatom frustules in natural habitats is often related to chemical contamination, as well as resulting from physical stress factors [24], features that have been used in various biomonitoring and ecological surveys of freshwater and marine ecosystems [24][25][26]. Separation and quantification of FA, which is directly related to developmental instabilities from DA, which represents the systematic asymmetry of populations, might therefore be useful in environmental applications of diatom morphology.…”
Section: Introductionmentioning
confidence: 99%